Co-financing irrigation water services: farmers' perspectives in the Mekong Delta, Vietnam - Nguyen Duc Kien; Pham Xuan Hung; Nguyen Hoang Diem My; Takeshi Mizunoya; Nguyen Cong Dinh (Journal of Agriculture and Environment for International Development)
Insufficient financial resources pose a considerable obstacle to Vietnam's endeavors to alleviate the repercussions of climate change. The adverse impacts of extreme weather events, particularly drought and water scarcity, have inflicted severe consequences on rice production across diverse regions, imperiling both the livelihoods of farmers and the nation's food security. While international aid is crucial, involving farmers in co-financing irrigation water services is essential for addressing these challenges in the long run. This study employs a blended approach encompassing quantitative and qualitative methodologies to investigate the determinants influencing farmers' willingness to participate in co-financing irrigation water services. Data were meticulously gathered through direct interviews with 289 farmers in An Giang province within the Mekong Delta, Vietnam. The findings underscore that the majority of respondents (86.16%) reported encountering water-related stresses in rice production, with 76.47% experiencing productivity losses attributable to extreme weather events. The results of the binary logistic regression model reveal significant factors associated with a farmer's decision to engage in co-financing irrigation services, including household income, participation in non-farm employment, farmers' perceptions of water scarcity, the adverse impact of water scarcity on rice yields, and the assessment of associated risks. Based on these discernments, we offer several policy recommendations aimed at facilitating the efficacious implementation of the irrigation water service co-financing initiative.